The purposefulness of the achievement in the statement of manifestation and clarification for Al-Jāḥiẓ - Khazraji, Abdul Baki Abdul Salam Al; Nasrallah, Mahdi Hassan (International Journal of Psychosocial Rehabilitation, 2020)
This study is at the heart of the deliberative theory, showing how the language is used according to the different contexts of speech and speech, in order to achieve the purposes of the communicators, and the realization of these purposes by the listeners, because the purpose is a deliberative context in the context of rhetorical action, Acts), founded by Austin (John Austen) and developed by his pupil (Serale Jogn Rogers), then expanded her field - in stages - to other researchers. Hence, this study is an attempt to show that the varied discourse in Abi Othman Ibn Bahr al-Jahiz (p. 255) is not a narrow statement of expression and news, but rather a discourse of authoritarian purposes.